2023
DOI: 10.1002/adfm.202303986
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Ni‐O‐C Heterogeneous Catalyst for Efficient Urea‐Assisted Hydrogen Production

Xuefei Xu,
Habib Ullah,
Muhammad Humayun
et al.

Abstract: Constructing multiple heterogeneous structures allows for improving the electrocatalytic activity of NiO by incorporating multiple active sites. Unfortunately, the poor conductivity of NiO makes efficient charge transfer within the heterogeneous structures difficult, thereby inhibiting the improvement of its intrinsic activity. Herein, F‐doped NiO/Ni@C heterogeneous catalyst (F‐NiO/Ni@C) is fabricated via a new organic‐inorganic hybrid approach, showing both advanced hydrogen evolution reaction (HER) and urea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…[4] However, most Ni-based compounds used as pre-catalysts require self-oxidation, and NiOOH is considered as the true active site for UOR. [5] The autoself-oxidation process of a catalyst not only increases the electrical energy consumption in the electrocatalytic process but also results in the dissolution of active metal sites, thereby reducing catalytic stability. To tailor catalysts without self-oxidation, a strong anchoring effect of the active sites is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…[4] However, most Ni-based compounds used as pre-catalysts require self-oxidation, and NiOOH is considered as the true active site for UOR. [5] The autoself-oxidation process of a catalyst not only increases the electrical energy consumption in the electrocatalytic process but also results in the dissolution of active metal sites, thereby reducing catalytic stability. To tailor catalysts without self-oxidation, a strong anchoring effect of the active sites is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al proposed a synthetic method for Fe-doped CoNiSe 2 nanosheets and discovered that the introduction of Fe ions promoted a charge redistribution between the cobalt and nickel, leading to enhanced kinetics for the OER . Apart from heteroatom doping, interfacial structural engineering of catalysts has also been proposed to be essential for the improvements of electrocatalytic performances. Liu et al reported on a nanowire catalyst composed of Co/CoO/Co­(OH) 2 , which exhibited a highly heterogeneous interface. The presence of strong chemical coupling at this hybrid interface was proposed to modulate the local electronic structure of the active centers, hence promoting the rapid charge transfer during the OER catalysis .…”
Section: Introductionmentioning
confidence: 99%
“…The combination of electrochemical water decomposition and new power generation technologies (solar, wind, etc.) is a good solution to this problem. In the process of water decomposition, the anode carries out the reaction of oxygen evolution reaction (OER) to produce oxygen and the cathode carries out the reaction of hydrogen evolution reaction (HER) to produce hydrogen, and there is no other pollutant formation in the whole process. , However, the energy barrier of electrochemical water decomposition is high, which requires the use of efficient catalysts to reduce energy consumption. The currently used electrocatalysts are generally precious metal-based catalysts with low earth reserves and high prices, which severely limit their industrial applications. , Therefore, it is important to find abundant and cheap electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%